Railway Ecology 2017
DOI: 10.1007/978-3-319-57496-7_1
|View full text |Cite
|
Sign up to set email alerts
|

Railway Ecology

Abstract: Railways play a major role in the global transportation system. Furthermore, railways are presently being promoted by several governments thanks to their economic and environmental advantages relative to other means of transportation. Although railways have clear advantages, they are not free of environmental problems. The objective of this book is to review, assess, and provide solutions to the impacts of railways on wildlife. We have divided the impacts of railways on biodiversity into four main topics: mort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
46
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 23 publications
0
46
0
2
Order By: Relevance
“…In general, the study of railway effects on wildlife has lagged far behind that of roads (Borda‐de‐Água et al. , Popp and Boyle ). Particularly in areas with complex topography, railways are often co‐aligned with roads and can impose similar negative effects on wildlife, such as mortality from train strikes (Kušta et al.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the study of railway effects on wildlife has lagged far behind that of roads (Borda‐de‐Água et al. , Popp and Boyle ). Particularly in areas with complex topography, railways are often co‐aligned with roads and can impose similar negative effects on wildlife, such as mortality from train strikes (Kušta et al.…”
Section: Introductionmentioning
confidence: 99%
“…Consideration of wildlife is an essential component of environmental impact assessments (EIAs), which evaluate the impacts of projects on the environment and provide suggestions for mitigation (El Haggar, ; Karlson et al, ). Due to their large home range and vulnerability to vehicles, large mammals are given special attention in EIAs, especially in the last two decades (Borda–de–Água, ; Popp & Boyle, ). However, in practice, mitigation strategies such as animal passes and vehicle speed limits are narrowly focused on the direct negative impacts of linear features (Karlson et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Railways are known to restrict gene flow in some amphibian species such as frogs or salamanders (e.g. Reh et al, 1990; Bartoszek and Greenwald, 2009) and many studies on train collision with wildlife reported a high abundance of amphibian kills (Borda-de Agua et al, 2017), representing up to 47 % of all vertebrate records (Heske, 2015). However, the railway in our study area had a low traffic density with approximately 10 trains/day, and train collisions may not be the only driver of the observed reduction in gene flow in A. obstetricans .…”
Section: Discussionmentioning
confidence: 99%
“…The railway was probably as attractive as the secondary road network for snakes, which may similarly explain gene flow enhancement observed in snakes. Railway embankments provide important alternative habitats for reptiles with optimal thermal conditions for basking (Graitson, 2006; Stoll, 2013; Borda-de Agua et al, 2017). Even active lines can harbour particularly high diversity in reptiles species (Graitson, 2006), notably because human presence is scarce and because reptiles can perceive vibrations transmitted through the rail tracks and the ballast when a train approaches, allowing them to reach a shelter before collision (Borda-de Agua et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation